Saving lives with fewer discussions - coordination between military and non-military organisations during disaster relief operations - Johan Stevens; Janjaap Semeijn; Cees Johannes Gelderman (The Central European Review of Economics and Management (CEREM), 2019)
Purpose: This study focusses on the coordination required between military and non-military organisations during humanitarian disasters.~Design / Research methods: An in-depth case study was conducted of the disaster relief operation after hurricane Matthew on Haiti in October 2016. We investigated the support of the Dutch military organization and its coordination with the non-military relief organizations. We examined coordination issues at operational, tactical, and strategic levels.~Findings: The study shows that no coordination problems occurred at operational level. At the tactical level, cultural differences between military and non-military organizations resulted in coordination problems and deviant perspectives on urgency. At the strategic level, there was a disagreement between the Dutch Ministry of Foreign Affairs and the Dutch Ministry of Defence regarding the Oslo Guidelines. A minority agreed that the guidelines actually apply to military organizations during disaster relief operations.~Practical implications: The coordination between the military organization and the non-military relief organization during disaster relief operations can be improved by promoting common and mutual respect and defining a clear tasks and role fulfilments. A first step to improve the coordination is to get familiarity and clarity on the Oslo Guidelines. Another step for improvement is for the military organization to accept that it has no leading but an assistance role during disaster relief operations.~Research limitations/implications: A single case study limits the external validity of the results, although useful insights were gained. Future research could address the role of the Oslo Guidelines during disaster relief operations. Are these guidelines still valid, should they be updated, and are the sufficiently known by all relief organizations, including the military?~Originality/value of the article: The world is faced with an increasing occurrence of disasters affecting human lives. More lives could be saved when military and non-military organizations would work together more effectively. This is one of the first studies to explore the terms of engagement at the start of relief operations.
Keywords: M4; 330; Disaster relief operations; humanitarian disaster; humanitarian logistics; military and non-military coordination